2021
DOI: 10.2147/jir.s323435
|View full text |Cite
|
Sign up to set email alerts
|

WNT16 is Robustly Increased by Oncostatin M in Mouse Calvarial Osteoblasts and Acts as a Negative Feedback Regulator of Osteoclast Formation Induced by Oncostatin M

Abstract: Background Bone loss is often observed adjacent to inflammatory processes. The WNT signaling pathways have been implicated as novel regulators of both immune responses and bone metabolism. WNT16 is important for cortical bone mass by inhibiting osteoclast differentiation, and we have here investigated the regulation of WNT16 by several members of the pro-inflammatory gp130 cytokine family. Methods The expression and regulation of Wnt16 in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…We recently discovered a novel mechanism whereby OSM-induced osteoclast differentiation can be balanced. We identified OSM and IL-6 as very strong stimulators of Wnt16 expression in primary mouse calvarial osteoblasts [ 14 ]. Human large-scale genome-wide association studies have identified the WNT16 locus as the strongest determinant of cortical bone mass and susceptibility to forearm fractures [ 110 , 111 ].…”
Section: Wnt16 As An Inhibitor Of Osm-induced Osteoclast Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently discovered a novel mechanism whereby OSM-induced osteoclast differentiation can be balanced. We identified OSM and IL-6 as very strong stimulators of Wnt16 expression in primary mouse calvarial osteoblasts [ 14 ]. Human large-scale genome-wide association studies have identified the WNT16 locus as the strongest determinant of cortical bone mass and susceptibility to forearm fractures [ 110 , 111 ].…”
Section: Wnt16 As An Inhibitor Of Osm-induced Osteoclast Formationmentioning
confidence: 99%
“…Mice with the Wnt16 gene deleted have increased numbers of osteoclasts [ 112 , 113 ], while mice with osteoblastic overexpression of Wnt16 have decreased osteoclast numbers [ 114 ]. Moreover, in vitro studies using cultures of human monocytes, mouse bone marrow macrophages and mouse spleen cells showed a direct inhibitory effect of WNT16 on RANKL-induced osteoclast differentiation [ 14 , 112 ]. In primary calvarial bone cell cultures containing osteoblasts and osteoclast progenitors, OSM, in addition to inducing Rankl mRNA expression and osteoclast differentiation, increased the expression of Wnt16 mRNA [ 14 ].…”
Section: Wnt16 As An Inhibitor Of Osm-induced Osteoclast Formationmentioning
confidence: 99%
See 3 more Smart Citations